Inferior Mesenteric Vein Thrombosis Resulting in Pylephlebitis in a Patient With Inflammatory Bowel Disease. Issue 11 (14th November 2022) - Becker, Erica C.; Grover, Dheera; Patel, Sanket; Dhakras, Purabi; Rossi, Lisa
ABSTRACT: Although uncommon, pylephlebitis is a life-threatening complication of mesenteric vein thrombosis. It is reported to affect adult men more commonly than women, with a median age of 57 years. Furthermore, few cases have been reported of pylephlebitis in patients with inflammatory bowel disease. Owing to low prevalence, there is a paucity of data regarding the diagnosis and management of pylephlebitis. Treatment approach ranges from conservative management (antibiotics and/or systemic anticoagulation) to surgical management. We report a case of a 62-year-old man diagnosed with inflammatory bowel disease with a course complicated by pylephlebitis of the inferior mesenteric vein managed successfully with antibiotics and anticoagulation.